Saran Aksi Saham Dengan Pendekatan Fundamental Dan Teknikal Menggunakan Metode Learning Vector Quantization Neural Network - I Made Gery Inggrayana; Wahyu Widodo; Luky Agus Hermanto (Fakultas Teknologi Informasi Institut Teknologi Adhi Tama Surabaya, 2016)
Stock is one instrument that is traded in the capital market. Investment in the form of shares can also offer enormous profit, even though it is highly risky in the investment especially on weekly stock trade.; Based on this reason, a system is developed to help take action in transactions whether to buy, sell or hold the stock. This analysis system uses technical and fundamental approach by applying Learning Vector Quantization (LVQ). This research uses five inputs taken from technical analysis, namely: Open Price, High Price, Low Price, Close Price, and Volume. One more input from the fundamental approach is Last Price. This system test indicated 72% accuracy on the transaction actions.